POTENTIAL LEGITIMACY CRISIS AND DEADLOCK OF LAW NUMBER 23 OF 2014 WITH CONSTITUTIONAL COURT DECISION NUMBER 135/PUU-XXII/2024 ON THE TERM OF OFFICE OF THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL - Dhimas Ari Yudha Pratama; Karlinae D. Bangas; Satriya Nugraha (International Journal of Cultural and Social Science, 2026)
This study aims to analyze the constitutional implications of Constitutional Court Decision Number 135/PUU-XXII/2024 on the term of office of the Regional People's Representative Council (DPRD), democratic legitimacy, and the potential for constitutional deadlock in the Indonesian state system. The main focus of the study lies in the conflicting norms between the principle of a five-year period of power as stipulated in Article 22E of the 1945 Constitution of the Republic of Indonesia and the consequences of the separation of National Elections and Regional Elections which have the potential to extend the term of office of the DPRD without renewing the electoral mandate. This study uses a normative legal research method (normative juridical) with a conceptual approach, a statutory approach, and a case approach. Data were obtained through a literature study of primary legal materials in the form of the 1945 Constitution of the Republic of Indonesia, Law Number 23 of 2014 concerning Regional Government, and Constitutional Court Decision Number 135/PUU-XXII/2024, and secondary legal materials from related literature and scientific journals. The analysis was conducted qualitatively with systematic, grammatical, and teleological interpretation techniques. The research findings indicate that the separation of elections without a clear transitional design creates normative tension between the obligation to implement the Constitutional Court's final and binding rulings and the principles of periodicity of power and legal certainty. This situation has the potential to trigger a crisis of democratic legitimacy within the Regional People's Representative Council (DPRD) and create a constitutional deadlock in regional governance. The implications of this research emphasize the importance of formulating a comprehensive constitutional transition framework and legislative reconstruction to maintain the consistency of constitutional supremacy, the circulation of power, and the quality of local democracy in Indonesia.